Exploring the effects and mechanisms of organophosphorus pesticide exposure and hearing loss - Zou, Mingshan; Huang, Mao; Zhang, Jianyun; Chen, Rong (Frontiers in Public Health, 2022)
Many environmental factors, such as noise, chemicals, and heavy metals, are mostly produced by human activities and easily induce acquired hearing loss. Organophosphorus pesticides (OPs) constitute a large variety of chemicals and have high usage with potentiate damage to human health. Moreover, their metabolites also show a serious potential contamination of soil, water, and air, leading to a serious impact on people's health. Hearing loss affects 430 million people (5.5% of the global population), bringing a heavy burden to individual patients and their families and society. However, the potential risk of hearing damage by OPs has not been taken seriously. In this study, we summarized the effects of OPs on hearing loss from epidemiological population studies and animal experiments. Furthermore, the possible mechanisms of OP-induced hearing loss are elucidated from oxidative stress, DNA damage, and inflammatory response. Overall, this review provides an overview of OP exposure alone or with noise that leads to hearing loss in human and experimental animals.